Interagency Collaboration in Regional Integration Policy-Making: A Systematic Literature Review - Mario de Araujo Chang; Eko Prasojo (PT. Global Research Collaboration, 2026)
This systematic literature review examines the determinants and governance dynamics shaping interagency collaboration in public sector policy-making, with particular attention to how existing scholarship addresses developing-country and regional integration governance contexts. The review addresses a critical gap in collaborative governance scholarship, whose empirical base remains heavily concentrated in high-income governance environments and therefore provides limited direct evidence on institutionally constrained governance settings. Using the PRISMA 2020 framework, a systematic search was conducted across Scopus, PubMed, Google Scholar, and Semantic Scholar, resulting in 22 empirical studies published between 2020 and 2025 that satisfied the inclusion criteria. The findings identify six major cross-cutting determinants of collaboration effectiveness: trust and reciprocity, informal coordination mechanisms, administrative coordination and information-sharing quality, organizational autonomy and collective accountability, mutuality and perceived shared benefits, and resource interdependence under policy complexity. The review also reveals a significant evidence gap, with only 9.1% of the included studies directly representing developing-country or non-OECD governance contexts. This indicates that existing interagency collaboration theories remain largely validated in high-income institutional settings and require further empirical examination in developing-country and regional integration contexts. The review’s primary theoretical contribution is the development of a dynamic feedback-loop model integrating Thomson and Perry’s (2006) collaboration dimensions with Gray’s (1989) antecedent conditions framework, demonstrating how successful collaboration may recursively reshape the institutional conditions enabling future collaboration. The study concludes that interagency collaboration should be understood as a multidimensional and adaptive governance process, while emphasizing that further empirical research is needed to test and refine these insights within developing-country and regional integration policy environments.